2021
DOI: 10.1002/acn3.51279
|View full text |Cite
|
Sign up to set email alerts
|

Increased atrial fibrillation risk in Parkinson’s disease: A nationwide population‐based study

Abstract: ObjectiveParkinson’s disease (PD) is the second most common neurodegenerative disorder associated with various morbidities. Although the relationship between cardiovascular disease and PD has been studied, a paucity of information on PD and atrial fibrillation (AF) association exists. Thus, we aimed to investigate whether patients with PD have an increased risk of AF.MethodsThis study included 57,585 patients with newly diagnosed PD (≥40‐year‐old, mean age 69.7 years, men 40.2%) and without a history of AF fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…PD patients often have prolonged atrial electromechanical delay, which is an independent predictor of atrial fibrillation [28]. In addition, previous studies have reported that PD was related to a higher risk of atrial fibrillation [29,30]. Further well-designed studies are warranted to explore the underlying mechanisms of PD in the development of IS and CES.…”
Section: Discussionmentioning
confidence: 99%
“…PD patients often have prolonged atrial electromechanical delay, which is an independent predictor of atrial fibrillation [28]. In addition, previous studies have reported that PD was related to a higher risk of atrial fibrillation [29,30]. Further well-designed studies are warranted to explore the underlying mechanisms of PD in the development of IS and CES.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of atrial fibrillation in PD patients was described by Han et al [17]. and Hong et al [26]; both studies used records from large population databases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AF has been strongly related to early-stage PD ( Hong et al, 2019 ). Moreover, Moon et al identified that patients with PD have an increased risk of AF, with a threefold increased risk (HR: 3.06, 95% CI: 1.20–7.77) of AF in younger PD patients (age: 40–49 years) ( Han et al, 2021 ). Observations of a cross-sectional PD patient cohort have identified abnormal blood flow patterns in brains ( Teune et al, 2014 ) and it is argued that AF-associated perturbation of the brain blood supply networks promotes tissue inflammation and damage leading to PD pathogenesis ( Junejo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%